The Green Screen Handbook : Real-World Production Techniques. - Foster, Jeff (Focal Press, 2015)
The Green Screen Handbook, Second Edition is a comprehensive how-to manual that walks you through the many integral techniques required in preproduction, production, and postproduction to use green screen effectively. Step-by-step instruction and time-saving tips cover matting and keying basics; lighting and digital camera essentials; setups using fabric, portable background panels, and paint; broadcast TV hardware switchers; professional HD and major motion picture compositing; multi-colored screen composites; directing storyboards and talent; working with virtual sets; motion tracking; and m.